2020
DOI: 10.1111/oik.07086
|View full text |Cite
|
Sign up to set email alerts
|

Dwarfism in close continental amphibian populations despite lack of genetic isolation

Abstract: Broggi provided crucial help for the standard metabolic rate experiment, G. Sánchez-Montes for the population genetics analysis, and C. Díaz Paniagua for skeletochronology and stable isotope analysis. I. Gomez-Mestre designed the experiments and supervised the whole process of preparing the manuscript. PermitsL. Hyeun-Ji was given permits to handle animals by the Andalusian state government (certificate nr. EXP-000337). DATA ACCESIBILITYData are archived in an institutional public repository (http://digital.cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Although they are not genetically isolated from other populations, the frogs in these arid areas are considerably smaller in body size (“dwarfs”) than the populations found in cooler and wetter areas of the Iberian peninsula. Hyeun‐Ji et al (2020) predicted that rTL would exhibit distinct developmental growth patterns, reaching sexual maturity at an earlier age due to their reduced growth rate. Although rTL was negatively related to body size and age across all populations, dwarfism and thus environment was not a predictor of telomere length (Hyeun‐Ji et al, 2020).…”
Section: Thermal Effects At the Level Of The Cell: Links To Telomere ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although they are not genetically isolated from other populations, the frogs in these arid areas are considerably smaller in body size (“dwarfs”) than the populations found in cooler and wetter areas of the Iberian peninsula. Hyeun‐Ji et al (2020) predicted that rTL would exhibit distinct developmental growth patterns, reaching sexual maturity at an earlier age due to their reduced growth rate. Although rTL was negatively related to body size and age across all populations, dwarfism and thus environment was not a predictor of telomere length (Hyeun‐Ji et al, 2020).…”
Section: Thermal Effects At the Level Of The Cell: Links To Telomere ...mentioning
confidence: 99%
“…Hyeun‐Ji et al (2020) predicted that rTL would exhibit distinct developmental growth patterns, reaching sexual maturity at an earlier age due to their reduced growth rate. Although rTL was negatively related to body size and age across all populations, dwarfism and thus environment was not a predictor of telomere length (Hyeun‐Ji et al, 2020).…”
Section: Thermal Effects At the Level Of The Cell: Links To Telomere ...mentioning
confidence: 99%
“…high seasonal pond desiccation risk), showed shorter telomeres than populations under lower desiccation risk (Burraco et al 2017). In another amphibian, the natterjack toad Epidalea calamita , a study across a continental case of dwarfism in Southern Spain found telomere differences between populations, but these did not match population variation in body size or habitat type and occurred in the absence of genetic isolation (Hyeun‐Ji et al 2020). Finally, a one‐year longitudinal common‐garden experiment investigated whether telomere dynamics, in the Sardinian tree frog Hyla sarda , differ in populations with contrasting biogeographic history (Canestrelli et al 2021).…”
Section: Telomere Dynamics Across Spatial Scalesmentioning
confidence: 99%
“…In Doñana, previous authors have reported a reduced body size in this and other amphibian species including Iberian newts Lissotriton boscai, spadefoot toads Pelobates cultripes and natterjack toads Epidalea calamita (e.g., Díaz-Paniagua et al 1996;Marangoni et al 2008). Local dwarfism seems to have evolved in response to environmental conditions (dry and warm environments) prevailing in this area (Hyeun-Ji et al 2020). In unfavorable or unpredictable environments, where adult mortality may be high, newts may increase their specific investment in reproduction at the expense of growth and mature at a younger age.…”
Section: Discussionmentioning
confidence: 55%